2022
DOI: 10.3390/ma15031041
|View full text |Cite
|
Sign up to set email alerts
|

Improving Polysaccharide-Based Chitin/Chitosan-Aerogel Materials by Learning from Genetics and Molecular Biology

Abstract: Improved wound healing of burnt skin and skin lesions, as well as medical implants and replacement products, requires the support of synthetical matrices. Yet, producing synthetic biocompatible matrices that exhibit specialized flexibility, stability, and biodegradability is challenging. Synthetic chitin/chitosan matrices may provide the desired advantages for producing specialized grafts but must be modified to improve their properties. Synthetic chitin/chitosan hydrogel and aerogel techniques provide the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 218 publications
(315 reference statements)
0
6
0
Order By: Relevance
“…To address this problem, numerous studies on suitable materials for skin repair have been conducted. Synthetic materials such as chitosan hydrogel (Yoon et al, 2017;Behr and Ganesan, 2022), crosslinked poly (N-vinylpyrrolidone) (PVP) hydrogel membranes (Thongsuksaengcharoen et al, 2020), and polyethylene glycol (PEG) hydrogel membranes have been reported to induce an appropriate response of skin reconstruction in a limited area (Chatterjee et al, 2019). However, synthetic materials are always associated with unsatisfying issues of poor biocompatibility, non-degradability, high cost, and complex fabrication methods, making it impossible to achieve mass production (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, numerous studies on suitable materials for skin repair have been conducted. Synthetic materials such as chitosan hydrogel (Yoon et al, 2017;Behr and Ganesan, 2022), crosslinked poly (N-vinylpyrrolidone) (PVP) hydrogel membranes (Thongsuksaengcharoen et al, 2020), and polyethylene glycol (PEG) hydrogel membranes have been reported to induce an appropriate response of skin reconstruction in a limited area (Chatterjee et al, 2019). However, synthetic materials are always associated with unsatisfying issues of poor biocompatibility, non-degradability, high cost, and complex fabrication methods, making it impossible to achieve mass production (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is important in gene therapy to maintain therapeutic concentrations over an extended period, improving treatment efficacy. [ 156 ] Biopolymer aerogels can provide a protective environment for encapsulated genetic material, shielding it from degradation by enzymes or other environmental factors. This protection is vital for maintaining the integrity and functionality of the delivered genes.…”
Section: Biopolymers Based Aerogels In Anticancer Drug Delivery Appli...mentioning
confidence: 99%
“…Chitosan hydrogels have weak mechanical strength, limiting their application as biomimetic materials. To improve the mechanical properties, chemical crosslinking The high versatility of CH/CS based materials is due to complex supramolecular structure resulting from packaging of macromolecules into long fibers, process dictated by the genetic code [199]. CS can form biocompatible hydrogels, with temperature [35,200] and pH [93,132] sensitive responses, antibacterial and anti-inflammatory activities [29,165,201], and self-healing behavior [29,165].…”
Section: Chitosan and Chitinmentioning
confidence: 99%